Pendampingan Guru dalam Meningkatkan Motorik Halus Anak Usia Dini Melalui Pembelajaran Kolase Menggunakan Bahan Alam - Setiadi, Kusno; Sutari, Sutari; Alma M. Djon (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
The purpose of this activity is to assist teachers in designing activities that can stimulate the fine motor skills of children in Early Childhood Education (PAUD) KB-Mawar, West Longkoga Village, Bualemo District, Banggai Regency. Method implementation is carried out in the form of direct face-to-face meetings between the activity implementers and the children of PAUD KB-Mawar. The implementation of this activity was carried out on January 25 to February 13, 2025. The desired end result of this activity is that teachers can enrich their skills in managing activities involving natural material media and deepen their understanding of children's fine motor skills.